The Mental Health of Refugee Children in Canada - Hyman, Ilene; Beiser, Morton; Vu, Nhi (Refuge: Canada's Journal on Refugees, 1996)
This paper reviews the literature onsources of stress, and the personal andsocial resources refugee youth use tocope with adversity. Preliminary findings fromthe Clarke Institute/Universityof Toronto Department ofPsychiatry Southeast Asian (SEA)Refugee Youth Project, a study of themental health and adaptation of SEAyouth to Canada, are used to supplementfindings from the literature. Thereview highlights research needs as wellas possibilities for programs that couldhelp promote the successful adaptationof refugee youth in Canada.